The Effectiveness of SAC in Learning Physics to Improve Student Learning Outcomes in Pandemic Covid-19 at Vocational Middle School 1 Baktiya, North Aceh - Qusthalani, Qusthalani (Universitas Syiah Kuala, 2021)
This study aims to identify the effectiveness of using SAC in distance learning physics. To see its effectiveness based on the value of creativity and student learning outcomes. This study usesquasi-experimental, there were two groups that were randomly selected, then given a pretest and after the next treatment was given a postest to find out whether there was a difference between the experimental group and the control group. The participants were all class X TKJ SMKN 1 Baktiya students in the first semester, totaling 37 students. The first treatment is using power point media as a learning resource. For the second treatment using SAC media in designing Android-based learning media. Data obtainedThe learning outcomes of students who are taught using instructional media are designed with an SAC of 70.55 and a standard deviation of 7.83. Meanwhile, using power point media the average student learning outcomes were 73.15 and a standard deviation was 7.49. Also obtained a sign price of 0.15 0.05 means that Ho is accepted. So it can be concluded that the use of SAC-based learning media is effective in increasing learning outcomes and student learning creativity during the Covid-19 pandemic.